The Systems of Judicial Procedures: Ecclesiastical Laws vis-a-vis Indian Civil Laws - Kaduppil, Roy Joseph (Iustitia, 2024)
This paper explores the comparative judicial procedures in ecclesiastical and Indian civil law, emphasizing their respective legal frameworks and philosophical foundations. It examines the structural distinctions between the adversarial and inquisitorial systems, highlighting how these systems operate in ensuring justice. The adversarial model, dominant in Indian civil law, is characterized by party-driven litigation, judicial neutrality, and procedural safeguards, whereas the inquisitorial system, prevalent in ecclesiastical law, prioritizes judicial-led investigations and a truth-seeking approach. The study further analyzes procedural overlaps, including the integration of inquisitorial elements in Indian law, and adversarial features within ecclesiastical tribunals. It also critically assesses the strengths and weaknesses of both systems, evaluating their efficiency, fairness, and potential for legal reform. The research underscores the evolving nature of legal frameworks, advocating for a balanced approach that enhances justice and procedural integrity.